Quick-hardening cement-based bridge deck pavement material and preparation method thereof

By using fast hard cement-based bridge deck paving materials, combined with raw materials such as sulfhydryl aluminate cement, silicate cement, etc., the problem of easy cracking of bridge deck paving materials is solved, and the early high strength and long-term stability of the material is achieved , extends service life and reduces maintenance costs.

CN119409463AInactive Publication Date: 2025-02-11SHANGHAI PEIHONG HIGHWAY MAINTENANCE TECH CO LTD

Patent Information

Application Number
CN202411546672.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing bridge deck paving materials are prone to cracks and other diseases under repeated vehicle loads, causing cracks in the bridge deck concrete paving layer, affecting service life and traffic efficiency, and frequent maintenance increases the maintenance workload.

Method used

It adopts fast-hard cement-based bridge deck paving materials, sulfur-containing aluminate cement, silicate cement, aggregate, fiber, mineral blend, early strength agent, redispersible latex powder, additives and coagulation agents. Through reasonable proportioning and mixing processes, the early strength and long-term stability of the material are improved.

Benefits of technology

The material has good fast hard and early strength properties, high bearing capacity in a short time, good early and long-term compressive strength, flexural strength and crack resistance, extend the service life of concrete, reduce the maintenance cost of bridge deck, reduce the number of maintenance times, and improve the Transportation efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of bridge deck pavement materials, and provides a quick-hardening cement-based bridge deck pavement material and a preparation method thereof. The quick-hardening cement-based bridge deck pavement material is prepared from the following components in specific parts by mass: sulphoaluminate cement, Portland cement, aggregate, fibers, a mineral admixture, an early strength agent, redispersible latex powder, an additive, a thickening time control agent and water. The bridge deck pavement material disclosed by the invention has good quick-hardening and early-strength performance, high bearing capacity within a short time and good bonding performance; the bridge deck pavement material is excellent in workability and good in early and long-term compressive strength, breaking strength and crack resistance, the service life of concrete is prolonged, and the maintenance cost of the bridge deck is reduced; the repairing agent is used for repairing a bridge deck pavement material, and can quickly recover traffic and reduce the influence on traffic passage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bridge deck paving materials, and in particular to a fast-hardening cement-based bridge deck paving material and a preparation method thereof. Background Art

[0002] At present, the pavement of highway bridges mainly adopts reinforced concrete + asphalt surface layer. Under the repeated action of vehicle loads, the concrete road and bridge deck will be damaged. Once the concrete cracks, the cracks will rapidly deteriorate, and cracks and other defects will appear in the concrete pavement of the bridge deck. After the bridge deck cracks, harmful ions in the rainwater will penetrate into the reinforced concrete main beam of the road and bridge and other structures, affecting the service life; it will also reduce the speed of vehicles, affect comfort, and reduce transportation efficiency. Generally, the damaged concrete needs to be chiseled out and re-paved. Conventional concrete materials have poor adhesion with the concrete of the beam body, and the interface strength is reduced. Maintenance is required, which has a great impact on traffic. The vibration caused by not interrupting traffic during the maintenance of urban bridges makes the maintenance effect poor, resulting in repeated repairs and failures. Repeated maintenance will deteriorate the concrete on the top of the beam body, greatly increasing the maintenance workload and affecting the life of the bridge.

[0003] For concrete paving repair materials, it is generally required to be fast-hardening and early-strengthening, not lower than or even higher than the compressive, flexural and tensile strength of the substrate, have sufficient bonding strength with the substrate, and have elastic modulus and linear expansion coefficient close to the substrate. Therefore, it is very necessary to develop high-performance bridge deck paving materials, which have the advantages of convenient construction, early strength, good interface, high toughness, impact resistance, and good structural durability. It is of great significance to reduce cracking diseases of road and bridge deck pavement layers, reduce the number of maintenance times, ensure normal traffic, and improve the efficiency of passenger and freight transportation. Summary of the invention

[0004] The purpose of the present invention is to provide a fast-hardening cement-based bridge deck paving material and a preparation method thereof in view of the deficiencies in the prior art.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a fast-hardening cement-based bridge deck paving material, comprising the following raw materials in parts by weight:

[0007] 20-30 parts of sulphoaluminate cement, 10-20 parts of Portland cement, 55-75 parts of aggregate, 5-8 parts of fiber, 10-15 parts of mineral admixture, 3-5 parts of early strength agent, 1-2 parts of redispersible latex powder, 1.2-2.5 parts of additives, 0.2-0.8 parts of setting agent and 13-18 parts of water.

[0008] Preferably, the aggregate comprises river sand and gravel, and the mass ratio of river sand to gravel is 2-4:1; the particle size of the river sand is 0.2-0.8 mm, and the fineness modulus is 1.22-1.68; the particle size of the gravel is 3-7 mm.

[0009] Preferably, the fibers include polypropylene fibers and / or steel fibers; the fibers have a diameter of 0.1 to 0.3 mm and a length of 15 to 30 mm.

[0010] Preferably, the mineral admixture comprises one or more of calcined coal gangue powder, fly ash and silica fume.

[0011] Preferably, the early strength agent is anhydrous sodium sulfate or lithium carbonate; and the redispersible latex powder comprises ethylene / vinyl acetate copolymer or vinyl acetate / versatate copolymer.

[0012] Preferably, the additive comprises a plastic expansion agent and a water reducer, the mass ratio of the plastic expansion agent to the water reducer is 2 to 3:1; the plastic expansion agent is calcium oxide, and the water reducer is a polycarboxylate water reducer.

[0013] Preferably, the setting regulator comprises a setting accelerator and a setting retarder, and the mass ratio of the setting accelerator to the setting retarder is 2 to 4:1; the setting accelerator comprises one or more of sodium aluminate, calcium aluminate and calcium fluoroaluminate, and the setting retarder comprises one or more of tartaric acid, sodium tetraborate and borax.

[0014] The present invention also provides a method for preparing the rapid-hardening cement-based bridge deck paving material, comprising the following steps:

[0015] 1) mixing sulphoaluminate cement, silicate cement, aggregate, mineral admixture, early strength agent, additive, setting regulator and water to obtain a mixture;

[0016] 2) The mixture, the fiber and the redispersible latex powder are mixed to obtain a fast-hardening cement-based bridge deck paving material.

[0017] Preferably, the mixing time in step 1) is 3 to 5 minutes, and the mixing speed is 200 to 300 r / min; the mixing time in step 2) is 2 to 4 minutes, and the mixing speed is 200 to 300 r / min.

[0018] The beneficial effects of the present invention include the following:

[0019] 1) Sulphoaluminate cement has a fast setting speed and high early strength, which ensures the rapid hardening and stability of the bridge deck. The later strength development is slow, but the long-term stability is good, and the frost resistance and impermeability are good, which improves the durability and service life of the bridge deck and plays an important role in special circumstances such as emergency repairs; the continued hydration of silicate cement can ensure the growth of later strength, and silicate cement is conducive to improving the durability of the structure. Mineral admixtures have filling and reinforcing effects. Calcined coal gangue powder, fly ash and silica fume as admixtures have the characteristics of high ductility, fast hardening and early strength, and can significantly improve the mechanical properties, durability and impermeability of bridge deck paving materials. Calcium oxide expansion agents and redispersible latex powders synergistically regulate the expansion coefficient and bonding durability of the material; fibers can reduce the shrinkage cracks of concrete and greatly improve the toughness and impact resistance of concrete.

[0020] 2) The present invention reasonably selects various raw materials, controls the amount of each raw material, etc., so that the bridge deck paving material obtained has good fast-hardening and early-strength performance, high bearing capacity in a short time, and good bonding performance; the bridge deck paving material has excellent workability, good early and long-term compressive strength, flexural strength, and crack resistance, extends the service life of concrete, and reduces the maintenance cost of the bridge deck; it is used for repairing bridge deck paving materials, which can quickly restore traffic and reduce the impact on traffic. DETAILED DESCRIPTION

[0021] The present invention provides a fast-hardening cement-based bridge deck paving material, comprising the following raw materials in parts by weight:

[0022] 20-30 parts of sulphoaluminate cement, 10-20 parts of Portland cement, 55-75 parts of aggregate, 5-8 parts of fiber, 10-15 parts of mineral admixture, 3-5 parts of early strength agent, 1-2 parts of redispersible latex powder, 1.2-2.5 parts of additives, 0.2-0.8 parts of setting agent and 13-18 parts of water.

[0023] The rapid-hardening cement-based bridge deck paving material of the present invention comprises 20 to 30 parts of sulphoaluminate cement, preferably 22 to 28 parts, more preferably 24 to 26 parts, and more preferably 25 parts.

[0024] The rapid hardening cement-based bridge deck paving material of the present invention comprises 10 to 20 parts of Portland cement, preferably 12 to 18 parts, more preferably 14 to 16 parts, and more preferably 15 parts.

[0025] The rapid hardening cement-based bridge deck paving material of the present invention comprises 55 to 75 parts of aggregate, preferably 60 to 70 parts, more preferably 63 to 67 parts, and even more preferably 65 to 66 parts.

[0026] In the present invention, the aggregate preferably comprises river sand and gravel, and the mass ratio of river sand to gravel is preferably 2-4:1, more preferably 2.5-3.5:1, and more preferably 3:1; the particle size of the river sand is preferably 0.2-0.8 mm, more preferably 0.3-0.7 mm, and more preferably 0.4-0.5 mm, and the fineness modulus is preferably 1.22-1.68, more preferably 1.32-1.61, and more preferably 1.45-1.51; the particle size of the gravel is preferably 3-7 mm, more preferably 4-6 mm, and more preferably 5 mm.

[0027] In the present invention, the particle sizes of river sand and gravel play an important role in the performance of bridge deck paving materials, and directly affect the compression resistance, durability and service life of the materials.

[0028] The rapid hardening cement-based bridge deck paving material of the present invention contains 5 to 8 parts of fibers, preferably 6 to 7 parts, and more preferably 6.5 parts.

[0029] In the present invention, the fibers preferably comprise polypropylene fibers and / or steel fibers; the diameter of the fibers is preferably 0.1 to 0.3 mm, more preferably 0.15 to 0.25 mm, more preferably 0.2 mm, and the length is preferably 15 to 30 mm, more preferably 20 to 25 mm, more preferably 22 to 23 mm.

[0030] The rapid hardening cement-based bridge deck paving material of the present invention comprises 10 to 15 parts of mineral admixture, preferably 11 to 14 parts, and more preferably 12 to 13 parts.

[0031] In the present invention, the mineral admixture preferably comprises one or more of calcined coal gangue powder, fly ash and silica fume.

[0032] The microscopic morphology of fly ash and silica fume is glassy and ball-shaped. When forming, the ball-shaped particles have a lubricating effect on the slurry. The fine particles can also fill the pores of the material to make the structure denser, which not only improves the compressive strength of cement, but also improves water resistance. Fly ash is used as volcanic ash in ordinary silicate cement. Through secondary hydration with cement hydration products, the silicate cement mortar structure can be made denser. Calcined coal gangue powder can partially replace cement, save cement resources, and promote the high-value utilization of coal gangue. Calcined coal gangue powder combines high ductility, fast hardening and early strength, which significantly improves the shortcomings of poor tensile deformation capacity of bridge deck paving materials. It can be efficiently used in bridge deck paving layers, reduce the risk of cracking of concrete paving layers, and increase the service life of bridge decks. In addition, the high-value utilization of solid waste can reduce the stacking of solid waste, and also contribute to environmental protection and sustainable utilization of resources, with significant economic and environmental benefits.

[0033] The rapid hardening cement-based bridge deck paving material of the present invention comprises 3 to 5 parts of an early strength agent, preferably 3.5 to 4.5 parts, and more preferably 4 parts.

[0034] In the present invention, the early strength agent is preferably anhydrous sodium sulfate or lithium carbonate.

[0035] The rapid-hardening cement-based bridge deck paving material of the present invention comprises 1 to 2 parts of redispersible latex powder, preferably 1.2 to 1.8 parts, and more preferably 1.4 to 1.5 parts.

[0036] In the present invention, the redispersible latex powder preferably comprises ethylene / vinyl acetate copolymer or vinyl acetate / versatate copolymer; the redispersible latex powder has good thickening and stability, helps to form a stable suspension system, and makes it difficult for the paving material to precipitate, stratify, etc. during the construction process; at the same time, it can also reduce the viscosity of the paving material and improve the construction efficiency; form a dense waterproof layer in the paving material, effectively prevent water penetration, thereby improving the impermeability of the paving material.

[0037] The rapid hardening cement-based bridge deck paving material of the present invention comprises 1.2 to 2.5 parts of additives, preferably 1.5 to 2.2 parts, and more preferably 1.8 to 2.0 parts.

[0038] In the present invention, the additive preferably comprises a plastic expansion agent and a water reducer, and the mass ratio of the plastic expansion agent to the water reducer is preferably 2 to 3:1, and more preferably 2.5:1; the plastic expansion agent is preferably calcium oxide, and the water reducer is preferably a polycarboxylate water reducer.

[0039] The rapid-hardening cement-based bridge deck paving material of the present invention comprises 0.2 to 0.8 parts of a setting regulator, preferably 0.4 to 0.6 parts, and more preferably 0.5 parts.

[0040] In the present invention, the setting regulator preferably comprises a setting accelerator and a setting retarder, and the mass ratio of the setting accelerator to the setting retarder is preferably 2 to 4:1, more preferably 2.5 to 3.5:1, and more preferably 3:1; the setting accelerator preferably comprises one or more of sodium aluminate, calcium aluminate and calcium fluoroaluminate, and the setting retarder preferably comprises one or more of tartaric acid, sodium tetraborate and borax.

[0041] In the present invention, the accelerator can shorten the setting time and improve the early strength, but it will cause the working performance of the concrete to decrease; adding a retarder can extend the setting time and enable the concrete to maintain better working performance; the retarder can effectively balance the setting time and working performance of the concrete while ensuring the quality of the project; adding the accelerator and the retarder at the same time can achieve rapid hardening and early high strength while ensuring the working performance of the concrete.

[0042] The rapid hardening cement-based bridge deck paving material of the present invention contains 13 to 18 parts of water, preferably 14 to 17 parts, and more preferably 15 to 16 parts.

[0043] The present invention also provides a method for preparing the rapid-hardening cement-based bridge deck paving material, comprising the following steps:

[0044] 1) mixing sulphoaluminate cement, silicate cement, aggregate, mineral admixture, early strength agent, additive, setting regulator and water to obtain a mixture;

[0045] 2) The mixture, the fiber and the redispersible latex powder are mixed to obtain a fast-hardening cement-based bridge deck paving material.

[0046] In the present invention, the mixing time in step 1) is preferably 3 to 5 minutes, more preferably 4 minutes, and the mixing speed is preferably 200 to 300 r / min, more preferably 250 r / min; the mixing time in step 2) is preferably 2 to 4 minutes, more preferably 3 minutes, and the mixing speed is preferably 200 to 300 r / min, more preferably 250 r / min.

[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0048] In the embodiment, the specific gravity of fly ash is 2.05-2.25, the particle size of silica ash is 0.3-0.5 μm, the particle size of calcined gangue powder is 1250 mesh, and the total mass content of alumina and silica in the calcined gangue powder is 78.4%. The sulphoaluminate cement is fast-hardening sulphoaluminate cement, and the silicate cement is 42.5R ordinary silicate cement.

[0049] Example 1

[0050] The fast-hardening cement-based bridge deck paving material is prepared from the following raw materials in parts by weight: 25 parts of sulphoaluminate cement, 15 parts of silicate cement, 65 parts of aggregate, 7 parts of fiber (steel fiber), 12 parts of mineral admixture, 4 parts of early strength agent (anhydrous sodium sulfate), 1.5 parts of redispersible latex powder (ethylene / vinyl acetate copolymer), 2 parts of additives, 0.5 parts of setting agent, and 15 parts of water; in the aggregate, the mass ratio of river sand to gravel is 3:1, and the particle size of river sand is 0.5mm, fineness modulus is 1.45, and the particle size of the stone is 5mm; the diameter of the steel fiber is 0.2mm and the length is 22mm; the mineral admixture is composed of calcined coal gangue powder, fly ash and silica fume in a mass ratio of 1:1:1; the additive is composed of a plastic expansion agent (calcium oxide) and a water reducer (solid polycarboxylic acid water reducer) in a mass ratio of 2.5:1; the setting regulator is composed of a setting accelerator (sodium aluminate) and a setting retarder (borax) in a mass ratio of 3:1.

[0051] Sulphoaluminate cement, silicate cement, aggregate, mineral admixture, early strength agent, additive, setting regulator and water are mixed at a speed of 250 r / min for 4 minutes to obtain a mixture; the mixture, fiber and redispersible latex powder are mixed at a speed of 250 r / min for 3 minutes to obtain a fast-hardening cement-based bridge deck paving material.

[0052] Example 2

[0053] The fast-hardening cement-based bridge deck paving material is prepared from the following raw materials in parts by weight: 22 parts of sulphoaluminate cement, 18 parts of silicate cement, 60 parts of aggregate, 8 parts of fiber (polypropylene fiber), 14 parts of mineral admixture, 3 parts of early strength agent (lithium carbonate), 1 part of redispersible latex powder (vinyl acetate / vinyl ester carbonate copolymer), 1.5 parts of additives, 0.4 parts of setting regulator, and 13 parts of water; in the aggregate, the mass ratio of river sand to gravel is 2.5:1, the particle size of river sand is 0.3 mm, the fineness modulus is 1.32, and the particle size of gravel is 6 mm; the diameter of polypropylene fiber is 0.15 mm, and the length is 18 mm; the mineral admixture is fly ash; the additive is composed of a plastic expansion agent (calcium oxide) and a water reducer (solid polycarboxylic acid water reducer) in a mass ratio of 2:1; the setting regulator is composed of a setting accelerator (calcium fluoroaluminate) and a retarder (tartaric acid) in a mass ratio of 3.5:1.

[0054] Sulphoaluminate cement, silicate cement, aggregate, mineral admixture, early strength agent, additive, setting regulator and water are mixed at a speed of 200 r / min for 5 minutes to obtain a mixture; the mixture, fiber and redispersible latex powder are mixed at a speed of 200 r / min for 4 minutes to obtain a fast-hardening cement-based bridge deck paving material.

[0055] Example 3

[0056] The fast-hardening cement-based bridge deck paving material is prepared from the following raw materials in parts by weight: 28 parts of sulphoaluminate cement, 12 parts of silicate cement, 70 parts of aggregate, 6 parts of fiber (steel fiber), 10 parts of mineral admixture, 5 parts of early strength agent (anhydrous sodium sulfate), 2 parts of redispersible latex powder (ethylene / vinyl acetate copolymer), 2.5 parts of additives, 0.6 parts of setting agent, and 17 parts of water; in the aggregate, the mass ratio of river sand to gravel is 3.5:1, and the particle size of river sand is The particle size of the stone is 3mm; the diameter of the steel fiber is 0.25mm and the length is 25mm; the mineral admixture is composed of calcined coal gangue powder and fly ash in a mass ratio of 1:1; the additive is composed of a plastic expansion agent (calcium oxide) and a water reducer (solid polycarboxylic acid water reducer) in a mass ratio of 2.5:1; the setting regulator is composed of a setting accelerator (calcium aluminate) and a setting retarder (sodium tetraborate) in a mass ratio of 2.5:1.

[0057] Sulphoaluminate cement, silicate cement, aggregate, mineral admixture, early strength agent, additive, setting regulator and water are mixed at a speed of 300 r / min for 3 minutes to obtain a mixture; the mixture, fiber and redispersible latex powder are mixed at a speed of 300 r / min for 2 minutes to obtain a fast-hardening cement-based bridge deck paving material.

[0058] Comparative Example 1

[0059] The sulphoaluminate cement in Example 1 was replaced by aluminate cement of equal mass, the mineral admixture and retarder were omitted, and the other conditions were the same as those in Example 1.

[0060] Comparative Example 2

[0061] The silicate cement, redispersible latex powder and fiber of Example 1 were omitted, the mineral admixture was changed to 8 parts, and the other conditions were the same as those of Example 1.

[0062] The compressive strength and flexural strength of the bridge deck paving materials of Examples 1 to 3 and Comparative Examples 1 to 2 were tested.

[0063] The bridge deck paving material of Example 1 has a 2h compressive strength of 33.9 MPa, a 5h compressive strength of 45.6 MPa, a 28d compressive strength of 78.5 MPa, a 2h flexural strength of 5.4 MPa, a 5h flexural strength of 8.1 MPa, and a 28d flexural strength of 11.6 MPa.

[0064] The bridge deck paving material of Example 2 has a 2h compressive strength of 32.6 MPa, a 5h compressive strength of 44.8 MPa, a 28d compressive strength of 76.8 MPa, a 2h flexural strength of 5.1 MPa, a 5h flexural strength of 7.3 MPa, and a 28d flexural strength of 10.8 MPa.

[0065] The bridge deck paving material of Example 3 has a 2h compressive strength of 33.5 MPa, a 5h compressive strength of 45.2 MPa, a 28d compressive strength of 77.9 MPa, a 2h flexural strength of 5.3 MPa, a 5h flexural strength of 7.7 MPa, and a 28d flexural strength of 11.2 MPa.

[0066] The bridge deck paving material of Comparative Example 1 has a 2h compressive strength of 22.1 MPa, a 5h compressive strength of 34.2 MPa, a 2h flexural strength of 3.5 MPa, and a 5h flexural strength of 5.9 MPa.

[0067] The bridge deck paving material of Comparative Example 1 has a 2h compressive strength of 20.5 MPa, a 5h compressive strength of 33.7 MPa, a 2h flexural strength of 3.1 MPa, and a 5h flexural strength of 5.3 MPa.

[0068] The present invention reasonably selects various raw materials, controls the amount of each raw material, etc., so that the obtained bridge deck paving material has good rapid hardening and early strength performance and high bearing capacity in a short time; the bridge deck paving material has excellent workability, good early and long-term compressive strength, flexural strength and crack resistance, prolongs the service life of concrete, and reduces the maintenance cost of the bridge deck.

[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A fast-hardening cement-based bridge deck paving material, characterized in that: Contains the following raw materials by mass: 20-30 parts of sulphoaluminate cement, 10-20 parts of Portland cement, 55-75 parts of aggregate, 5-8 parts of fiber, 10-15 parts of mineral admixture, 3-5 parts of early strength agent, 1-2 parts of redispersible latex powder, 1.2-2.5 parts of additives, 0.2-0.8 parts of setting agent and 13-18 parts of water.

2. The rapid hardening cement-based bridge deck paving material according to claim 1, characterized in that: The aggregate comprises river sand and gravel, the mass ratio of river sand to gravel is 2-4:1; the particle size of the river sand is 0.2-0.8 mm, and the fineness modulus is 1.22-1.68; the particle size of the gravel is 3-7 mm.

3. The rapid hardening cement-based bridge deck paving material according to claim 1 or 2, characterized in that: The fibers include polypropylene fibers and / or steel fibers; the fibers have a diameter of 0.1 to 0.3 mm and a length of 15 to 30 mm.

4. The rapid hardening cement-based bridge deck paving material according to claim 3, characterized in that: The mineral admixture comprises one or more of calcined coal gangue powder, fly ash and silica fume.

5. The rapid hardening cement-based bridge deck paving material according to claim 4, characterized in that: The early strength agent is anhydrous sodium sulfate or lithium carbonate; the redispersible latex powder contains ethylene / vinyl acetate copolymer or vinyl acetate / versatate copolymer.

6. The rapid hardening cement-based bridge deck paving material according to claim 4 or 5, characterized in that: The additive comprises a plastic expansion agent and a water reducing agent, wherein the mass ratio of the plastic expansion agent to the water reducing agent is 2 to 3:1; the plastic expansion agent is calcium oxide, and the water reducing agent is a polycarboxylic acid water reducing agent.

7. The rapid hardening cement-based bridge deck paving material according to claim 6, characterized in that: The setting regulator comprises a setting accelerator and a setting retarder, wherein the mass ratio of the setting accelerator to the setting retarder is 2 to 4:1; the setting accelerator comprises one or more of sodium aluminate, calcium aluminate and calcium fluoroaluminate, and the setting retarder comprises one or more of tartaric acid, sodium tetraborate and borax.

8. The method for preparing the rapid-hardening cement-based bridge deck paving material according to any one of claims 1 to 7, characterized in that: The following steps are included: 1) mixing sulphoaluminate cement, silicate cement, aggregate, mineral admixture, early strength agent, additive, setting regulator and water to obtain a mixture; 2) The mixture, the fiber and the redispersible latex powder are mixed to obtain a fast-hardening cement-based bridge deck paving material.

9. The preparation method according to claim 8, characterized in that: The mixing time of step 1) is 3 to 5 minutes, and the mixing speed is 200 to 300 r / min; the mixing time of step 2) is 2 to 4 minutes, and the mixing speed is 200 to 300 r / min.

Citation Information

Patent Citations

  • Super-early-strength high-ductility cement based composite material and preparation method thereof

    CN107140921A

  • Bridge widening material with no requirement of traffic interruption

    CN109721316A

  • UHPC bridge deck pavement structure and preparation method thereof

    CN114134809A

  • Ecological high-ductility cement-based rapid repairing material prepared from calcined coal gangue powder and method

    CN115745536A

  • Early-strength ultrahigh-toughness cement-based material and preparation method thereof

    CN115974500A

Cited By

  • A high-performance cement-based composite material for repair and reinforcement engineering and preparation method thereof

    CN119774960A